2010
DOI: 10.1590/s0102-79722010000300002
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre sintomatologia psicopatológica, adesão ao tratamento e qualidade de vida na infecção HIV e AIDS

Abstract: ResumoO presente estudo observou a existência de relações significativas entre sintomatologia psicopatológica (BSI), adesão ao tratamento (CEAT-VIH) e qualidade de vida (WHOQOL-Bref) em 125 pessoas HIVpositivo/AIDS em tratamento antirretroviral, atendidos em um hospital do Porto (Portugal). A sintomatologia psicopatológica correlacionou-se negativamente com adesão ao tratamento e qualidade de vida, e a adesão ao tratamento associou-se positivamente com a qualidade de vida. O modelo preditor de adesão ao tratam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 19 publications
(19 reference statements)
3
8
0
9
Order By: Relevance
“…Other authors 13,36 found negative correlations between the presence of depressive symptoms and anxiety with quality of life. Reis et al 37 highlighted that psychopathological symptoms negatively affect quality of life and adherence to antiretroviral treatment. Moreover, the literature reports that increased levels of stress and depression accelerate the deterioration of the immune system and disease progression 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Other authors 13,36 found negative correlations between the presence of depressive symptoms and anxiety with quality of life. Reis et al 37 highlighted that psychopathological symptoms negatively affect quality of life and adherence to antiretroviral treatment. Moreover, the literature reports that increased levels of stress and depression accelerate the deterioration of the immune system and disease progression 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the instrument is available in six language versions with a bilingual user's manual (Spanish/English), and published psychometric information is available for several countries as Brazil, Chile, Colombia, Mexico, Panama, Peru, Portugal, Puerto Rico, Romania, and Spain (Remor, 2013). Thus, the questionnaire has been used as a measure of adherence in other several studies (e.g., Lorscheider, Geronimo, & Colacite, 2012;Reis, Lencastre, Guerra, & Remor, 2010;Remor, Penedo, Shen, & Schneiderman, 2007) The PRO measure CEAT-VIH is a multidimensional instrument including items targeting behavioral indicators of adherence (i.e., during the past week, from the beginning of treatment, in relation to the medication schedule, global selfevaluation, and accuracy of remembering current medication), and also focus on determinants of adherence: antecedents of nonadherence behaviors (i.e., feeling physically better, feeling worse, feeling sad or depressed), doctorpatient interaction (i.e., frequency of doctor's reinforcement of adherence behaviors, global assessment of the quality of the relationship), patient's beliefs regarding the adherencerelated effort, time, degree of difficulty, self-efficacy, and outcome expectations, patient's perception of side-effects intensity, level of personal knowledge regarding medication, satisfaction with treatment, improvements in health attributed to treatment (Remor, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, it is not only necessary to think about the means to fight HIV/AIDS, but also how seropositive living affects the lives and well being of those infected by it. With this in mind, over the last years there has been an increase in academic interest regarding the connection between HIV/AIDS and the quality of life of HIV+ individuals (3)(4)(5) . The World Health Organization's (6) definition of quality of life comprises an individual's perception regarding his or her position in life.…”
Section: Introductionmentioning
confidence: 99%
“…Studies (1,4,5,8) have shown that the analysis of quality of life within an HIV/AIDS context is very important, because it enables HIV+ individuals to express the perception they have regarding their lives and provides health professionals with better means of treating the adversities resulting from the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation